Evaluating the effect of a mild cycling heating period on leukocyte coping capacity in growing pigs - Byrd, Christopher J.; Young, Jennifer M. (Frontiers in Animal Science, 2023)
This study evaluated whether leukocyte coping capacity (LCC) could be an effective method for detecting physiological stress in growing pigs who are exposed to a mild cycling heating period. We hypothesized that whole blood samples collected from pigs exposed to high environmental temperatures would exhibit a reduced respiratory burst response [measured in relative light units (RLU) using chemiluminescence, where reduced RLU levels indicate a smaller respiratory burst size] compared to pigs that were only exposed to thermoneutral temperatures. A secondary objective was to determine the time required for LCC whole blood samples to reach their maximal RLU value following in vitro challenge using phorbol-12-myristate 13-acetate (PMA) to induce a respiratory burst. Forty growing pigs (mean 66.7 kg; range: 54.9 – 87.5 kg) were assigned to 1 of 2 treatments: 1) heat stress (HS; n = 20), or 2) thermoneutral (TN; n = 20). The HS pigs experienced a cycling mild heat stress period over 48 h (range: 19.5-28.6°C), while TN pigs were exposed to thermoneutral temperatures (range: 18.9-23.7°C). Whole-blood samples were collected via jugular venipuncture at 0, + 4, +8, +24, and +48 h relative to the start of the cycling heating period and were artificially challenged using PMA. Samples were measured at 0, + 15, and +30 min relative to in vitro challenge. No differences were observed between HS and TN treatments (P = 0.67) and no treatment by hour interaction was detected (P = 0.48). Maximal RLU values were obtained at 15 min post-PMA challenge (P < 0.05).